Anther, ovule and embryological characters in Velloziaceae in relation to the systematics of Pandanales - Sajo, Maria das Graças [UNESP]; Mello-Silva, Renato; Rudall, Paula J. (Cambridge University Press (CUP), 2011)
Velloziaceae are a monocot family of five genera and c. 250 species (Mello-Silva, 2009). The family is now assigned to the order Pandanales, a small but morphologically diverse monocot order of five families: Cyclanthaceae, Pandanaceae, Stemonaceae (including Pentastemona Steenis), Triuridaceae and Velloziaceae (APG III, 2009). Within Velloziaceae, three genera occur in South America, of which two are endemic to Brazil (Barbacenia Vand., Vellozia Vand.) and the third is Andean (Barbaceniopsis L.B.Sm.). A fourth genus, Xerophyta Juss., grows in tropical Africa and the fifth, Acanthochlamys P.C.Kao, is endemic to China. In this chapter, we present new data on the anther, ovule and embryology of Velloziaceae in the context of ongoing related studies on floral evolution (e.g. Sajo et al., 2010) and the systematics of Pandanales (Furness and Rudall, 2006; Rudall and Bateman, 2006). Earlier studies on ovule and seed development and androecial features were used to delimit the genera of Velloziaceae (Menezes, 1976, 1980). Embryological features of Pandanales are currently poorly known, though some studies suggest that they are potentially systematically useful. For example, Cheah and Stone (1975) reported an unusual megagametophyte in some Pandanus species, in which nucellar nuclei migrate into the developing embryo sac, and tapetum type is unusually variable within Pandanales (Furness and Rudall, 2006).